HILIRISASI PRODUK HASIL AKUAKULTUR UNTUK MENINGKATKAN NILAI TAMBAH PETANI IKAN DAN PENYEDIAAN PANGAN BERGIZI DI NAGAN RAYA, PROVINSI ACEH - Rinawati, Rinawati; Fadhillah, Radhi; Rozi, Anhar; Zulfadhli, Zulfadhli (Universitas Mataram, 2025)
Nagan Raya is a district with significant potential in freshwater aquaculture. Local economic development in this region can be advanced through existing community business groups. One such group is UPR Mina Mandiri, a fish farming business located in Beutong Sub-district, Nagan Raya. However, this group faces several challenges in the post-harvest period, including unstable fish prices during the peak harvest season leading to oversupply and price drops, limited knowledge of proper post-harvest handling techniques, and a lack of effective marketing strategies. This Community Service Program (PKM) aimed to enhance the added value of tilapia aquaculture through product downstreaming for the Mina Mandiri Group. The methods used in this PKM included presentations and hands-on demonstrations. Evaluation results indicated a significant increase in the participants' understanding, with an average improvement of 65-70% across all indicators. The downstreaming activities successfully resulted in two value-added products: frozen tilapia and fish nuggets, marketed under the brand names